Pengelolaan Sampah Berkelanjutan melalui Pendampingan Pembuatan Pupuk Kompos dari Sampah Rumah Tangga di Desa Cileles Kecamatan Jatinangor Kabupaten Sumedang - Nooraini, Afni (Civitas Consecratio: Journal of Community Service and Empowerment, 2024)
The waste problem is still a chore that hasn’t been solved till today in every region, including in Cileles Village, Sumedang Regency. Cileles Village has not managed organic waste optimally. So, the authors carried out Community Service (PkM) activities in Cileles Village related to assisting in making compost from household waste, namely organic waste, for the community in Cileles Village. The aim of this PkM is to increase public education regarding waste management, make the community more independent in managing household waste, reduce the volume of waste at the Cibeureum TPA and improve the community’s income. The method used in this PkM is socialization and practical work on making compost from household waste directly. The result of PkM is that the community understands sustainable waste management and is able to make compost from their own household waste.